2015
DOI: 10.1242/dev.120212
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid signaling spatially restricts osteoblasts and controls ray-interray organization during zebrafish fin regeneration

Abstract: The zebrafish caudal fin consists of repeated units of bony rays separated by soft interray tissue, an organization that must be faithfully re-established during fin regeneration. How and why regenerating rays respect ray-interray boundaries, thus extending only the existing bone, has remained unresolved. Here, we demonstrate that a retinoic acid (RA)-degrading niche is established by Cyp26a1 in the proximal basal epidermal layer that orchestrates ray-interray organization by spatially restricting osteoblasts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 22 publications
1
44
1
Order By: Relevance
“…The Shha-driven Hh/Smo signaling we observed in a narrow distal band of neighboring basal epidermis and Obs does not adequately explain the widespread proliferation block observed when exposing regenerating zebrafish to the Smo-inhibitor cyclopamine (Blum and Begemann, 2015;Lee et al, 2009;Quint et al, 2002;Wehner et al, 2014). We surmise that this phenotype, which is the primary evidence supporting the hypothesis that Hh promotes regenerative outgrowth, is an off-target effect similar to that reported when using cyclopamine to study zebrafish germ cell development (Mich et al, 2009).…”
Section: Ihha Is Required To Promote Mineralization Of Regenerated Bonementioning
confidence: 52%
See 1 more Smart Citation
“…The Shha-driven Hh/Smo signaling we observed in a narrow distal band of neighboring basal epidermis and Obs does not adequately explain the widespread proliferation block observed when exposing regenerating zebrafish to the Smo-inhibitor cyclopamine (Blum and Begemann, 2015;Lee et al, 2009;Quint et al, 2002;Wehner et al, 2014). We surmise that this phenotype, which is the primary evidence supporting the hypothesis that Hh promotes regenerative outgrowth, is an off-target effect similar to that reported when using cyclopamine to study zebrafish germ cell development (Mich et al, 2009).…”
Section: Ihha Is Required To Promote Mineralization Of Regenerated Bonementioning
confidence: 52%
“…The Smo small-molecule inhibitor cyclopamine arrests proliferation of multiple cell types in the regenerate (Blum and Begemann, 2015;Lee et al, 2009;Quint et al, 2002;Wehner et al, 2014), suggesting Hh/Smo signaling contributes to general regenerative outgrowth. Furthermore, ihha is robustly expressed in blastemal Obs during regeneration (Avaron et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, shha expression was reported to become downregulated upon immersion of fish in RA (Laforest et al, 1998), suggesting that the inhibitory effect of RA on preosteoblast differentiation might be at least partly due to interfering with Hh signaling. However, we found that, although expression of shha requires an RA-free epidermal niche established by Cyp26a1, inhibition of Hh signaling does not interfere with preosteoblast differentiation but rather blocks proliferation (Blum and Begemann, 2015).…”
Section: Discussionmentioning
confidence: 74%
“…3D; data not shown). Notably, RA or R115866 treatment does not interfere with preosteoblast migration (Blum and Begemann, 2015), strongly suggesting that the absence of preosteoblasts in the blastema of RA-or R115866-treated fish is due to dedifferentiation failure. Together, our data reveal that RA signaling inhibits the switch from mature osteoblasts to proliferating preosteoblasts and demonstrate that Cyp26b1 activity is crucially required for osteoblast dedifferentiation (Fig.…”
Section: Osteoblast Dedifferentiation Requires Inactivation Of Ra By mentioning
confidence: 98%
“…This difference may be due to genetic or morphological differences among species. However, RA signaling is important for fin development and regeneration (67)(68)(69)(70). We identified several members of the RA signaling pathway with opposing patterns of differential expression along the proximodistal axis of uninjured fins.…”
Section: Discussionmentioning
confidence: 99%